Trypanosoma cruzi: Maintenance in Culture Modify Gene and Antigenic Expression of Metacyclic Trypomastigotes - Víctor T Contreras; Ana Rita De Lima; Gelu Zorrilla (Memorias do Instituto Oswaldo Cruz, 1998)
In this study we examined whether the maintenance of Trypanosoma cruzi by long-time in axenic culture produces changes in gene expression and antigenic profiles. The studies were made with a Dm30L-clone from a low-virulent strain and a non-cloned virulent EP-strain of T. cruzi. Both parasites were maintained, for at least seven years, by successive alternate passage triatomine/mouse (triatomine condition), or by serial passage in axenic medium (culture condition). The comparison of the [35S]methionine metabolic labeling products of virulent and non-virulent parasites by 2D-SDS-PAGE, clearly indicates that the expression of metacyclic trypomastigotes (but not of epimastigotes) proteins have been altered by laboratory maintenance conditions. Western blot analysis of EP and Dm30L-epimastigotes using a serum anti-epimastigotes revealed that although most of antigens are conserved, four antigens are characteristics of triatomine condition parasites and three other are characteristics of culture condition parasites. Anti-metacyclics serum revealed significative differences in EP- and Dm30L-metacyclic trypomastigotes from triatomine condition. However, avirulent metacyclic forms were antigenically very similar. These results suggest that besides a possible selection of avirulent subpopulation from T. cruzi strains genetically heterogeneous when maintained by long time in axenic culture, changes in virulence might be due to post-translational modifications of the antigens induced by the absence of the natural alternability (vertebrate-invertebrate) in the life-cycle of T. cruzi